O uso do software geogebra como ferramente pedagógica no estudo de funções quadráticas em turmas de 9º ano do ensino fundamental do CMF - Souza, Francisco Ademir Lopes de (2012)
This research aimed to analyze if the use of GeoGebra software as educational tool improved the pupil learning of quadratic functions in the 9th grade of the Elementary School in The Military School of Fortaleza (CMF). For this purpose, a study on the foundations of Mathematics Education as occupation and area of knowledge was undertaken as well as its relation to educational software use in the process of teaching and learning up to and including the use of GeoGebra software. This study was based mainly on Miorim (1998), Borba (1999), Fiorentini and Lorenzato (2007), Preiner (2008) and Nóbriga and Araújo (2010). Two groups of 9th grade were experienced, called Investigation and Comparison groups. In the first group GeoGebra software was explored for quadratic functions studies, part of the studies took place in the computer lab. The second group did not use the software. After the experience both groups were submitted to the same test and the first group answered a questionnaire. With data collected and observations carried out during the experience, qualitative and quantitative approaches were made. It is concluded that the software is easy managing, facilitates and promotes the process of learning with good acceptance by the most of students. Furthermore, the software helps students to get their own conclusion concerning the learning of quadratic functions, comparing the result of the groups experienced, it was notorious a better performance of students from Investigation group than students of Comparison group.